A CASE SERIES OF THE PIGGYBACK DISEASE CHARACTERIZED BY BLACK ESCHAR FOLLOWING COVID-19 RHINO-ORBITAL CEREBRAL MUCORMYCOSIS. - Acharya, Souvagini; Behera, Sharmistha; Sahu, Alaka; Pradhan, Asmita; Panda, Braja Behari; Purohit, Somy (Student’s Journal of Health Research Africa, 2024)
Purpose This case series focused on examining the clinical profile of individuals suspected of having Post post-COVID mucormycosis. These patients were admitted with the presence of black eschar on their face and eyes. Methods This case series includes six individuals who were suspected to have post-COVID Mucormycosis. They presented with black eschar. The cases were examined over six months, from May 2021 to October 2021, at the Ophthalmology Department of Veer Surendra Sai Institute of Medical Sciences and Research (VIMSAR), Burla. Results All the cases included in the case series exhibited symptoms of black eschar and were in the age group of over 40 years. All the cases had a history of Type II Diabetes mellitus (T2DM) in their medical records. Two individuals had undergone oxygen therapy and steroid therapy as part of their treatment for COVID-19. In addition, one case had a previous admission to the Intensive Care Unit (ICU). Upon admission, all patients underwent Diagnostic Nasal Endoscopy (DNE) and were subsequently administered liposomal amphotericin B (AMB) for 21 days, followed by oral Posaconazole. Two patients underwent skin grafts, while another patient required exenteration. Unfortunately, four patients did not survive, but there were positive outcomes for three patients who experienced improved visual activity. Additionally, two patients only had the disease affecting one eye. Conclusion The simultaneous occurrence of T2DM, a history of steroid use, and oxygen therapy were significant factors contributing to the development of post-COVID Mucormycosis. Despite implementing timely interventions, the mortality rate for post-COVID mucormycosis was significant, reaching approximately 50%. Indeed, a fungus in the realm of viruses caused widespread devastation.